2020
DOI: 10.1016/j.heliyon.2020.e05501
|View full text |Cite
|
Sign up to set email alerts
|

Biological synthesis of gold and silver nanoparticles using leaf extracts of Crassocephalum rubens and their comparative in vitro antioxidant activities

Abstract: The use of plant and plant products in the synthesis of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) is made possible because of the natural inherent phytochemicals responsible for the reduction of respective metallic salts to nanoparticle forms, and ensuring therapeutic applicability. In this study, synthesis of AgNPs and AuNPs was performed using two different aqueous extraction methods for Crassocephalum rubens: maceration using laboratory method of extraction (cold aqueous extract of Crassoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Such a clear change of color confirms the reduction of metals to the nano form. Similar changes have been observed by Thiruchelvi et al [ 26 ] and Adewale et al [ 27 ]. These authors [ 27 ] synthesized AgNPs and AuNPs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Such a clear change of color confirms the reduction of metals to the nano form. Similar changes have been observed by Thiruchelvi et al [ 26 ] and Adewale et al [ 27 ]. These authors [ 27 ] synthesized AgNPs and AuNPs.…”
Section: Resultssupporting
confidence: 91%
“…Similar changes have been observed by Thiruchelvi et al [ 26 ] and Adewale et al [ 27 ]. These authors [ 27 ] synthesized AgNPs and AuNPs. According to the researchers colour changes suggest reduction and the synthesis of the nanoparticles, which are related to the surface plasmon resonance (SPR) band.…”
Section: Resultssupporting
confidence: 91%
“…The plant-mediated synthesis is economical and make use of readily available and renewable plant materials such leaves, stems, roots, etc. Moreover, synthesis occurs in just one step, since the phytochemicals are able to act as reducing, capping, and stabilizing agents [110][111][112]. Previous studies have confirmed the safety of the biogenic method for MNP synthesis with effective antimicrobial activities against MDR bacteria [112,113].…”
Section: Nps With Antimicrobial Activity and Their Mode Of Actionmentioning
confidence: 98%
“…Likewise, Aftab et al (2021;2022); Aftab et al (2020) have reported that Cu-doped NiO thin films convey incredibly good anti-fungal as well as anti-bacterial characteristics. Furthermore, there are numerous other reports present in the literature in which other metals nanoparticles and their oxides have been used as antimicrobial agents (Aljabali et al, 2018;Roy et al, 2019;Adewale et al, 2020;Chand et al, 2020;Pachaiappan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%